2015
DOI: 10.1007/s11468-015-9980-8
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary Optical Transmission Exhibited by Surface Plasmon Polaritons in a Double-Layer Wire Grid Polarizer

Abstract: We fabricate a double-layer wire grid polarizer (WGP) and perform optical characterization to clarify the relationship between the structural and polarization characteristics. For normal incidence, the fabricated double-layer WGP exhibits an extinction ratio of 30.4 dB for a period of 400 nm. The transverse magnetic transmittance peak angle is found to vary with the period of the WGP. The peak shift can be explained on the basis of the extraordinary optical transmittance phenomena exhibited by the surface plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…To solve this problem, we propose a plasmonic filter using the propagating surface plasmon polariton in a wire grid (WG) structure. In a previous study, experiments demonstrated by designing the structure of the doublelayer WG structure, the extraordinary transmission can be achieved at a specific incident angle and light wavelength [1,2]. In addition, results of transmittance mapping indicate that transmission phenomena can be explained by the propagating surface plasmon polariton in the double-layer WG structure.…”
Section: Introductionmentioning
confidence: 92%
“…To solve this problem, we propose a plasmonic filter using the propagating surface plasmon polariton in a wire grid (WG) structure. In a previous study, experiments demonstrated by designing the structure of the doublelayer WG structure, the extraordinary transmission can be achieved at a specific incident angle and light wavelength [1,2]. In addition, results of transmittance mapping indicate that transmission phenomena can be explained by the propagating surface plasmon polariton in the double-layer WG structure.…”
Section: Introductionmentioning
confidence: 92%
“…However, we experimentally demonstrated the detection of a high refractive index medium (n = 1.546-1.700) using surface plasmon sensors for the first time [11]. Our previous study on a double-layer wire grid polarizer with a grating structure [12,13] showed that extraordinary transmission [14] occurred at the interface between the metal and the contact medium. Similar phenomena may occur in the surface plasmon sensor with a 1D metal grating structure.…”
Section: Introductionmentioning
confidence: 92%
“…In several studies [38][39][40][41] it was shown that the peak positions are determined by the periodicity of the holes. The periodicity is usually comparable to the wavelength of the incident light.…”
Section: Applications In Biological and Chemical Sensingmentioning
confidence: 99%